2021
DOI: 10.3389/fonc.2021.664809
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Multiple-Organs Injuries Following ICI Treatment With Tislelizumab in an Advanced Non-Small Cell Lung Cancer Patient: A Case Report

Abstract: Immune-related adverse events (irAEs) following treatment with immune checkpoint inhibitors (ICIs) can affect almost any organ systems. Multiple-organs irAEs are a rare occurrence which makes its management and treatment very challenging. This is a case report of a 71-year-old man with advanced non-small cell lung cancer (NSCLC) who developed multiple-organs irAEs (lung, muscle, myocardium, liver, and pituitary) after a single cycle (21 days) of the BGB-A317 (Tislelizumab). After more than two months of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…After a review of 1,258 citations in PubMed and the Cochrane Library, 14 case reports, including 14 patients, met the selection criteria of our systematic review ( Saibil et al, 2019 ; Salem et al, 2019 ; Shirai et al, 2019 ; Giancaterino et al, 2020 ; Lie et al, 2020 ; Matsui et al, 2020 ; Todo et al, 2020 ; Xing et al, 2020 ; Cao et al, 2021 ; Deng et al, 2021 ; Hu et al, 2021 ; Jespersen et al, 2021 ; Yang et al, 2021 ; Shindo et al, 2022 ) ( Figure 5 ). The clinical characteristics and prognosis of the 14 patients are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…After a review of 1,258 citations in PubMed and the Cochrane Library, 14 case reports, including 14 patients, met the selection criteria of our systematic review ( Saibil et al, 2019 ; Salem et al, 2019 ; Shirai et al, 2019 ; Giancaterino et al, 2020 ; Lie et al, 2020 ; Matsui et al, 2020 ; Todo et al, 2020 ; Xing et al, 2020 ; Cao et al, 2021 ; Deng et al, 2021 ; Hu et al, 2021 ; Jespersen et al, 2021 ; Yang et al, 2021 ; Shindo et al, 2022 ) ( Figure 5 ). The clinical characteristics and prognosis of the 14 patients are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A summary about irAEs of tislelizumab in clinical trials is shown in Figure 4 ; myocarditis and myositis are not observed. Only one recent case reported multiple organ injuries following tislelizumab treatment in an advanced non-small cell lung cancer patient ( 21 ), while in this case, myocarditis is less severe, and there is not enough reference for us to follow. Our patient presented a rare tislelizumab-related myocarditis, accompanied by myositis and other organ injuries, which also intuitively showed the severity of ICI-associated irAEs to cardiologists like us.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that worse clinical outcomes were observed in patients who discontinued ICIs than in continuously treated patients (18)(19)(20)(21). Considering the durable anti-tumor effect of ICI rechallenge reported in several case reports (22)(23)(24), the clinical benefit of restarting ICI has received widespread consideration The efficacy and safety of ICI rechallenge were first explored in melanoma (25). Pollack et al enrolled 80 melanoma patients who discontinued ICIs due to severe irAEs and showed high rates of recurrent or distinct toxicities (12).…”
Section: Discussionmentioning
confidence: 99%